Struktur Indang Tigo Sandiang di Kecamatan Patamuan Kabupaten Padang Pariaman - Sitinur Fazura; Nerosti Nerosti (SENDRATASIK UNP, 2022)
This study aims to describe and analyze the structure of Tigo Sandiang's Indang in Patamuan District, Padang Pariaman Regency. This type of qualitative research using descriptive analytical method. Instruments in the researcher's own research using supporting instruments such as writing equipment, photo cameras, and mobile phones. The types of data used are primary data and secondary data. Data collection techniques used are literature studies, observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, displaying data, and drawing conclusions/verification. The results of this study indicate that the structure of Indang Tigo Sandiang consists of 3 Indang groups, namely Indang in Patamuan District, VII Koto Sungai Sarik, and Lubuk Alung. Each group performed alternately at different times but still in a triangular formation. The third group of Indang discussed the theme of overseas people returning home together after the outbreak of the covid 19 virus. The distinctive feature of Indang Tigo Sandiang is singing while moving, with the same six patterns of movement in the three Indang groups and has twelve kinds of movements in Patamuan and Subdistricts. LubukAlung. However, there are eleven kinds of motion in District VII Koto Sungai Sarik, because the motion in Indang Tigo Sandiang is determined by one of the attractors, namely the artisan or the person who transfers the motion, in which the movement can be reversed. Each group has dance elements, namely movement, creator, top design, dramatic design, group composition, theme, music, fashion make-up and props. Based on these dance elements, it can be seen that these elements are interrelated and related to each other.